Socio-economic Dimension of the Sustainable Development of Polish Provinces - Wyrwa, Joanna; Barska, Anetta; Jędrzejczak-Gas, Janina; Kubiak, Piotr (European Journal of Sustainable Development, 2022)
The aim of this article was to conduct research and present the results of a ratio analysis assessing the implementation of the concept of sustainable development in Polish provinces. It suggests a set of indicators tracking two of the areas of sustainable development: economic and social, in two separate periods: before the 2019 pandemic and during the 2020 pandemic. In addition to determining the performance of Lubusz Province compared to other provinces, the authors’ assumption is also to identify the impact of the COVID-19 pandemic on the implementation of economic and social sustainability goals in Poland as a whole. The key issues concerning the concept of sustainable development and the state of research on sustainability indicators at a regional level are presented with the help of literature review. On the basis ratio analysis was rated economic development of 16 Polish provinces was assessed and then benchmarked to determine the position of Lubusz Province. The proposed tracking indicators included the following aspects: economic potential, innovation of the economy, sustainable production patterns, demographic changes, job market, and social integration. The obtained results answered the question concerning the socio-economic development of Polish provinces, in particular that of Lubusz Province, in the context of sustainability before and during the pandemic. Keywords: socio-economic development, a ratio analysis, COVID-19 pandemic.